2011
DOI: 10.1016/j.healthplace.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the obesogenic environment of North East England

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 45 publications
2
42
1
2
Order By: Relevance
“…Results of the present study showed, firstly, that neighbourhood street connectivity was not significantly associated with adults' BMI after adjusting for key individual level characteristics. While not the first UK-based study to show null associations between street connectivity and obesity (e.g., Burgoine et al, 2011), findings are at odds with findings of a number of previous studies that have examined associations of obesity with markers of walkability defined using administratively-defined buffer zones (e.g., Doyle et al, 2006;Spence et al, 2008), as was the approach used here. There are several possible explanations for these discrepant findings.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Results of the present study showed, firstly, that neighbourhood street connectivity was not significantly associated with adults' BMI after adjusting for key individual level characteristics. While not the first UK-based study to show null associations between street connectivity and obesity (e.g., Burgoine et al, 2011), findings are at odds with findings of a number of previous studies that have examined associations of obesity with markers of walkability defined using administratively-defined buffer zones (e.g., Doyle et al, 2006;Spence et al, 2008), as was the approach used here. There are several possible explanations for these discrepant findings.…”
Section: Discussioncontrasting
confidence: 88%
“…The authors of the review, and others (Lake and Townshend, 2006), have identified the lack of evidence from outside of the US as problematic, since associations of the built environment with obesity may vary across countries. Findings from one study based in North East England and published since the 2010 review showed null associations between street connectivity and body mass index (BMI), further underscoring the importance of additional investigation outside of the US (Burgoine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Though the research base has burgeoned, exploring environmental influences on both physical activity and diet within the same study remains relatively rare, though international examples exist 53 and a number of themes have been highlighted. For example, an Australian study highlighted that high stress levels found in socially disadvantaged neighbourhoods were associated with poor weight management, less physical activity during leisure time, and frequent fast food consumption in women 54 .…”
Section: Considering Both Pa and Food Environmentsmentioning
confidence: 99%
“…However, it is possible to show that children living closer to parks and recreational spaces are less likely to experience weight gain (24). Moreover, the availability of food outlets in the neighborhood was not necessarily associated with unhealthy diets but was associated with higher consumption of fruit per day (25).…”
Section: Obesogenic Environmentsmentioning
confidence: 97%